Pengaruh Relaksasi Otot Progresif Terhadap Tingkat Stress pada Remaja di Lapas Anak Blitar - Ariyanto, Eko April (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
The purpose of this study was to proves if there is a relaxation effect on reducing stress in adolescents who live in prison of child Blitar. The study design used was post test only group design with adolescent subjects who were undergoing punishment in prison of child Blitar. Total of subject 61 adolescents divided into 31 control group and the experimental group of 30 selected by random sampling. Research data collect with DSI Scale (Daily Stress Inventory) were prepared by Brandey & Jones (1989), and self-report were reported at the time before and after the implementation of relaxation. Statistical analysis was performed using statistical nonparamentrik Mann Whitney U test. Statistical test results show the value of Z = 416.500 at p = 0.484 (p> 0.05). This shows that the data post-test between the control group and the experimental group showed no significant difference. Therefore the research hypothesis which says there is a relaxation effect can reducing the level of stress in prison of child Blitar not proven.